Ecological coefficient of performance (ECOP) optimization for an irreversible Brayton heat engine with variable-temperature thermal reservoirs - Ust, Y; Sogut, OS; Sahin, B; Durmayaz, A (ELSEVIER SCI LTD, 2006)
An ecological performance analysis for an irreversible Brayton heat engine with variable-temperature thermal reservoirs based on the ecological criterion called Ecological Coefficient of Performance (ECOP) is presented. The model considered includes irreversibilities due to finite-rate heat transfer and internal dissipations. The effects of design parameters such as isentropic temperature ratio, heat exchanger effectiveness, thermal reservoir inlet temperature ratio and the ratio of hot-to-cold thermal capacity rates of thermal reservoirs, on the general and optimal ecological performances have been investigated in detail. Comparisons of the results with those of an alternative ecological objective function defined in the literature, the maximum power output conditions, and thermal efficiency are also provided.
Keywords: Brayton heat engine; irreversibility; ecological optimization; performance analysis; variable-temperature thermal reservoir; ENTROPY GENERATION MINIMIZATION; MAXIMUM POWER-DENSITY; THERMODYNAMICS; CRITERION; Energy & Fuels